A method of evaluating the topographical effect on atmospheric dispersion using a numerical model. (1st January 2001) - Ichikawa, Y.; Sada, K.
A method of evaluating topographical effects on exhaust gas dispersion using a numerical model is proposed. The numerical model consists of a turbulence closure model and a Lagrangian particle dispersion model. The topographical effect was evaluated in terms of the ratios of maximum concentration and the distance of the point of maximum concentration from the source on the topography to the respective values on a flat plane and the relative concentration distribution along the ground surface plume axis normalised for the maximum concentration on a flat plane. The proposed method was applied to the prediction of the dispersion of exhaust gas from a thermal power plant in a complex terrain. Good agreement was obtained between topographical effects evaluated by the numerical model and wind tunnel experiments.